Analisis Faktor-Faktor yang Memengaruhi Auditor Switching : Studi Empiris pada Prusahaan Energi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Herberd Glorianto Wadu; Sarlin P. Nawa Pau; Maria. P. L. Muga (Dharma Ekonomi, 2024)
This study aims to analyze the factors that influence auditor switching. The population of this study are energy sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The data used in this study were obtained through internet research (online research) on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. This research uses a quantitative approach. The sample was determined by purposive sampling method. The data analysis used in this research is descriptive statistics and logistic regression. The results of this study indicate that profitability, going concern opinion, company size, and financial distrees have no effect on auditor switching.